ANALISIS USAHA TAMBAK IKAN BANDENG (Chanos chanos) DAN UDANG WINDU (Penaeus monodon) DI DESA BABULU LAUT KECAMATAN BABULU LAUT KABUPATEN PENAJAM PASER UTARA - Siti Munazirah; Helminuddin; Elly Purnamasari (2339-1324, 2017)
This study aimed to analyze the financial farms, calculate the sensitivity of farms, calculate the breakeven point on the aspect of price, production and sale of farms, and knowing the marketing channels and marketing agencies of farming fish and tiger shrimp in District Babulu Penajam Paser Utara.Methods of sample used is purposive sampling with the number of respondents taken as many as 10 people who conduct business activities in aquaculture. This study was conducted in April 2016 and April 2017. The data analysis method used is the financial method Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit Cost Ratio (BCR Net), Period of Return on Investment (Payback period), sensitivity analysis (sensitivity analisys) and break-even analysis in the form of a breakeven price, the breakeven point of production, sales breakeven point. The results of this study indicate that further aquaculture fish and tiger shrimp is feasible to be implemented over the period of next five years. The results of the sensitivity analysis of the cultivation of making a profit in the next five years with the current market economic conditions Rp. 593,052,658.00. The actual condition of cultivation based on aspects of production, sales and pricing in general is above the conditions BEP (Break Event Point) with an average value of 5.65. Marketing channels 0 rate of aquaculture No 2 is 0 Rate (cultivators - Consumer) and two levels, namely (cultivators - Wholesalers - Wholesalers Retailers - Consumer).